PROCESS PLANNING AND WEIGHTED SCHEDULING WITH WNOPPT WEIGHTED DUE-DATE ASSIGNMENT USING HYBRID SEARCH FOR WEIGHTED CUSTOMERS - Demir, Halil Ibrahim; Cil, Ibrahim; Uygun, Ozer; Simsir, Fuat; Kokcam, Abdullah Hulusi (MATTER: International Journal of Science and Technology, 2016)
Although scheduling with due date assignment and, integrated process planning and scheduling are two popular topics studied by researchers, there are few works on the integration of process planning, scheduling, and due date assignment. In this study integration of process planning and scheduling with the weighted due date, the assignment is studied. Different level of integration of these three functions is tested. As a solution techniques random search and hybrid search are applied. The hybrid search starts with random search and continues with the genetic search. Search results are compared with ordinary solutions and searches are found very useful and hybrid search outperformed random search. Hybrid search with full integration combination found as the best combination.